2012
DOI: 10.1029/2012jg001951
|View full text |Cite
|
Sign up to set email alerts
|

Distribution characteristics of transparent exopolymer particles in the Pearl River estuary, China

Abstract: ). In the field study, Ca 2+ concentration had a positive correlation with TEP color concentration in the surface layer with salinity <16. Decrease of TEP concentration seaward from intermediary salinity was partly due to dilution of seawater as well as enhanced aggregation and sedimentation of TEP via increasing divalent cation concentration. TEP concentration and turbidity maximum coexisted at the tip of salt wedge in the bottom layer during the wet season, and positive correlation between TEP and turbidity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 75 publications
5
29
0
Order By: Relevance
“…Although no previous information on TEP distribution exists for this area, previous studies in similarly productive areas or during phytoplankton blooms already observed high TEP concentrations (Long and Azam, 1996;Harlay et al, 2009;Klein et al, 2011). The TEP levels we measured at the SWAS are generally within the range of those reported for coastal areas (Passow and Alldredge, 1995;Riebesell et al, 1995;Kiorboe et al, 1996;Hong et al, 1997;Jähmlich et al, 1998;Wild, 2000;Ramaiah et al, 2001;Engel et al, 2002b;García et al, 2002;Radic et al, 2005;Scoullos et al, 2006;Sugimoto et al, 2007;Harlay et al, 2009;Wurl et al, 2009;Harlay et al, 2010;Fukao et al, 2011;Klein et al, 2011;Sun et al, 2012;Van Oostende et al, 2012;Dreshchinskii and Engel, 2017;Jennings et al, 2017). Only two studies, in the western Baltic Sea and the Dona Paula Bay (Arabian Sea), reported TEP levels higher than ours (Engel, 2000;Bhaskar and Bhosle, 2006).…”
Section: )supporting
confidence: 50%
“…Although no previous information on TEP distribution exists for this area, previous studies in similarly productive areas or during phytoplankton blooms already observed high TEP concentrations (Long and Azam, 1996;Harlay et al, 2009;Klein et al, 2011). The TEP levels we measured at the SWAS are generally within the range of those reported for coastal areas (Passow and Alldredge, 1995;Riebesell et al, 1995;Kiorboe et al, 1996;Hong et al, 1997;Jähmlich et al, 1998;Wild, 2000;Ramaiah et al, 2001;Engel et al, 2002b;García et al, 2002;Radic et al, 2005;Scoullos et al, 2006;Sugimoto et al, 2007;Harlay et al, 2009;Wurl et al, 2009;Harlay et al, 2010;Fukao et al, 2011;Klein et al, 2011;Sun et al, 2012;Van Oostende et al, 2012;Dreshchinskii and Engel, 2017;Jennings et al, 2017). Only two studies, in the western Baltic Sea and the Dona Paula Bay (Arabian Sea), reported TEP levels higher than ours (Engel, 2000;Bhaskar and Bhosle, 2006).…”
Section: )supporting
confidence: 50%
“…Moreover, estuaries present in highly human populated areas tend to see a large input of nitrogen and phosphorus including from agriculture‐ and aquaculture‐related activities (Lacerda, ). These changing physico‐chemical conditions can act as stressors for resident microbial communities (Paerl, Valdes, Peierls, Adolf, & Harding, ; Sun et al, ). In coastal ecosystems such as mangroves, plant matter serves as an additional source of organic matter in nearby aquatic systems (Dittmar et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In estuaries, in addition to temperature and light, factors that potentially control primary production are forced by tide variability and also by river runoff and nutrient inputs (Sun et al 2012). At a small scale, tidal regimes play a fundamental role in phytoplankton dynamics, as the movement of water masses causes notable variations in salinity, and in SPM and nutrient concentrations (Monbet 1992;Jouenne et al 2007;Gameiro and Brotas 2010).…”
Section: Accepted Manuscriptmentioning
confidence: 99%